Secondary metabolites produced by Colletotrichum lupini, the causal agent of anthachnose of lupin (Lupinus spp.). (3rd May 2020) - Masi, Marco; Nocera, Paola; Boari, Angela; Zonno, Maria Chiara; Pescitelli, Gennaro; Sarrocco, Sabrina; Baroncelli, Riccardo; Vannacci, Giovanni; Vurro, Maurizio; Evidente, Antonio
ABSTRACT: Colletotrichum lupini: is the causal agent of lupin ( Lupinus albus L.) anthracnose, a destructive seed-borne disease affecting stems and pods. Despite that several biological studies have been carried out on this pathogen, the production of secondary metabolites has not yet been investigated. Thus, a strain of C. lupini, obtained from symptomatic stems of L. albus, has been grown in vitro to evaluate its ability to produce bioactive compounds. From its culture filtrates, a 3-substituted indolinone, named lupindolinone, and a 5, 6-disubstituted tetrahydro-α-pyrone, named lupinlactone, were isolated together with the known (3 R )-mevalonolactone and tyrosol. Lupindolinone and lupinlactone were characterized as 3-ethylindolin-2-one and 5-hydroxy-6-methyltetrahydropyran-2-one by spectroscopic methods (essentially nuclear magnetic resonance [NMR] and high-resolution electrospray ionization mass spectrometry [HR ESI-MS]). The R absolute configuration (AC) at C-5 of lupinlactone was determined by applying the modified Mosher's method. Thus, considering its relative stereochemistry assigned by NMR spectroscopy, the AC of lupinlactone could be formulated as 5 R, 6 S . Lupindolinone was isolated as racemic mixture as shown by investigation using chiroptical methods. The metabolites were assayed in different biological tests and proved to have some activities at the used concentration.